Characterization of Neutron and Gamma Beams at the TRIGA 2000 Reactor Beam Ports Using Monte Carlo - Rasito Rasito; Sidik Permana; Ilham Y (Institut Teknologi Bandung, 2019)
Neutron and gamma beams characterization at the beam ports of TRIGA 2000 reactor was done in order to prepare the development of Prompt Gamma Neutron Activation Analysis (PGNAA) facility. Characterization was performed by simulation using Monte Carlo method with MCNPX and PHITS computer codes. The MCNPX code is used to simulate the neutron-gamma fluence and spectra of the reactor core from fission reactions. The PHITS code is used to simulate the distribution of the neutron-gamma fluence in the beam ports. The simulation was done by modeling the geometry and elemental composition of reactor material and radiation source model in the form of fission reaction in the reactor core. This results will be used to select the most suitable one of the four beam ports for the PGNAA use, based on the prescribed requirements, such as the neutron spectral characteristics and neutron-gamma fluence ratio at the beam port’s outlet. The results indicate that the tangential beam port provides better characteristics of neutron spectrum and neutron-gamma fluence ratio so become most suitable for PGNAA facility.